A history of the sugar and cement cartels in twentieth-century Spain. Issue 3 (1st September 2020) - Rosado-Cubero, Ana; Martínez-Soto, Angel
ABSTRACT: In twentieth-century Spain, many industries were cartelised, and successfully created and maintained long-standing, mutually beneficial relationships with the State. This article describes two: the Spanish based sugar and cement cartels. In the case of sugar, controlling foreign imports was the key to survival of the General Association of Sugar Manufacturers (Sociedad General Azucarera, SGA). Although small 'non-associated' companies survived and competed with it, the cartel became strong when the three main sugar producers agreed not to compete and negotiated with the Spanish Government on tariff protection. In the more cohesive cement industry, a cartel was formed by the six largest companies and they presented a united front to the Ministry of Industry. From 1941 the cement cartel mainly sought, and received, support via production sharing (attending to the requests of the Franco's regime) and participating in domestic price control.